PENERAPAN HUKUMAN MATI BAGI KORUPTOR DALAM PERSPEKTIF ISLAM DI INDONESIA - Maswandi Maswandi (Universitas Medan Area, 2016)
The application of the death penalty in Indonesia is the most severe punishments were applied to cases which are considered an extraordinary crime (extra-ordinary crime) as the case Terrorists, Drug, Makar and Corruption, the death penalty has a foundation as stipulated in Article 10 letter a figure 1e of the Code of Penal. In corruption cases are death penalty as stipulated in Article 2 paragraph (2) of Law No. 31 of 1999 amended by Law No. 20 of 2001 on Corruption Eradication. Despite the threat of the death penalty for criminals, but in fact until now none of the Decision of the Court of Corruption (Corruption) in Indonesia who dared break the criminals with death sentences, but quite clearly both national law or in the perspective of Islam to justify the enactment of punishment die for criminals who commit corruption under certain circumstances and the perpetration of crimes that can be destructive to the life of the nation.